First frost - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2024)
"Following the events of The Longmire Defense, we return to find Walt and our familiar cast of characters from Abaroska county tasked with solving a crime even more challenging than the last. Walt Longmire returns in this twentieth installment of the award-winning and bestselling series that has been a hit on both the page and the screen. Set in the unpsoiled countryside of Wyoming, Sheriff Walt Longmire has to navigate his own increasingly complicated personal life with the ever-changing and often violent underworld that encroaches on what was once referred to as the Old West. This time, he is up against a sinister plot that could hurt the people closest to him and forever change the way he sees his beloved Wyoming"--